Autophagy–virus interplay in plants: from antiviral recognition to proviral manipulation. (9th August 2019) - Kushwaha, Nirbhay Kumar; Hafrén, Anders; Hofius, Daniel
Summary: Autophagy is a conserved self‐cleaning and renewal system required for cellular homeostasis and stress tolerance. Autophagic processes are also implicated in the response to 'non‐self' such as viral pathogens, yet the functions and mechanisms of autophagy during plant virus infection have only recently started to be revealed. Compelling evidence now indicates that autophagy is an integral part of antiviral immunity in plants. It can promote the hypersensitive cell death response upon incompatible viral infections or mediate the selective elimination of entire particles and individual proteins from compatible viruses in a pathway similar to xenophagy in animals. Several viruses, however, have evolved measures to antagonize xenophagic degradation or utilize autophagy to suppress disease‐associated cell death and other defence pathways like RNA silencing. Here, we highlight the current advances and gaps in our understanding of the complex autophagy–virus interplay and its consequences for host immunity and viral pathogenesis in plants.